2015
DOI: 10.1590/1678-6765
|View full text |Cite
|
Sign up to set email alerts
|

Diagnóstico etiológico de enfermidades do sistema nervoso central de equinos no Estado de Minas Gerais, Brasil

Abstract:  RESUMOO Brasil possui o quarto maior rebanho equino do mundo, e o Estado de Minas Gerais detém o maior número de equinos do país. Portanto, um diagnóstico preciso das doenças neurológicas dos equinos é prioridade no estado. Sendo assim, o objetivo deste estudo foi identificar, utilizando a Reação em Cadeia pela Polimerase (PCR), os agentes infecciosos responsáveis por enfermidades que afetam o sistema nervoso central (SNC) de equinos. De janeiro de 2009 a janeiro de 2011, foi realizado um levantamento dos ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…Similarly, Costa et al (2015) found conflicting results between these tests using brain material from the equine species. Concordance between FAT and MIT was excellent for both cattle (0.97) and horses (0.94).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Costa et al (2015) found conflicting results between these tests using brain material from the equine species. Concordance between FAT and MIT was excellent for both cattle (0.97) and horses (0.94).…”
Section: Resultsmentioning
confidence: 99%
“…Viremia persists for at least 14 days, which is a prerequisite for EHM, allowing the transport of the virus to the CNS, as well as the risk factors that determine its occurrence, where infection of endothelial cells occurs, but the mechanism underlying CNS endothelial infection is unknown, as are the risk factors that determine its occurrence, initiating an inflammatory cascade, vasculitis, microthrombosis and extravasation of mononuclear cells, resulting in perivascular cuffing and local hemorrhage. 3,1 .…”
Section: Theme Summarymentioning
confidence: 99%
“…The most common clinical signs are ataxia and flaccid paresis of the hind limbs. 2,6,1 , in addition to hypotonia of the tail and anus, and urinary incontinence 2,6,5 .…”
Section: Theme Summarymentioning
confidence: 99%
“…Um levantamento da raiva equina no Piauí, entre 2007 a 2011, revelou 2,8% (1/35) de casos positivos [15]. Por outro lado, em Minas Gerais, Costa et al [4] demonstraram que, entre 2009 a 2011, houve 21,7% (47/217) de equinos positivos para raiva pela técnica de Imunofluorescência direta (IFD) e prova biológica. Na Paraíba, entre 2002 a 2008 foram verificados 6,9% (11/159) casos positivos dentre os equinos encaminhados para atendimento veterinário [13].…”
Section: Introductionunclassified